Caracterización del riesgo cambiario en la empresa Indufaros S.A. (2012)
In this paper, we will try to expose how the Currency Exchange Risk will affect Indufaros S.A, given the increasing globalization tendencies and increased International Capitals dynamics. We will also keep in mind, the international exchange markets, short term and medium term fluctuations involved in the company’s financial decisions. This will let us know how they are performing on currency exchange operations with the purpose of developing a comprehensive model of this activity with the result of lower currency and cash flow risks. This will be the result of a complete study of historical-statistical background of the country`s Foreign Exchange policies, complemented with the company`s particularities to provide adequate Hedge against this risks so they can maintain a positive cash flow indicator